Redesign e adaptação de jogo de tabuleiro - Muller, André (2012)
This following document aims to describe and to support the project completion, which consists of the redesign of the game Detective. This document will be reported theoretical and creative process for the preparation of the redesign, with references, and other graphics that were relevant in the development of the project. Creating even a parallel between the process of developing the curriculum of the course in Graphic Design Technology, UTFPR, under the guidance of prefessor Kando Fukushima to work discipline of certification.